A construção de um problema social : o caso do "pó preto" e seu debate nas audiências públicas de licenciamento ambiental em Vitória/ES - Pinheiro, Larissa Franco de Mello Aquino (2012)
An overview of the construction of an old social problem which is the air pollution generated by the enterprises located at Ponta do Tubarão and its effect on the city of Vitoria is presented. Fruit of the great developmental projects installed in the city from the 1960s on, such problem brings certain risks that have already met opposition by the population. In this topic, the targets of the analysis were the public hearings for environmental licensing which took place in Vitoria (ES) when there was a Production Expansion in Vale s Complex of Pelletizing (Plant VIII), in 2006, departing from the idea that they are public arenas where different social actors (State, businesses, and society to be impacted), who support distinct interests such as rationality, values, and projects related to the dispute for a social space, confront each other. It was investigated the way this form of social mobilization happen in the political arena that is called public hearings, that is, the way a social problem becomes visible and an object of mobilization. It was observed that the several social actors who take part in the public arena contend for spaces to broadcast their speeches and to position themselves in regard to the issues, thus revealing distinct discursive capacities, which become a differential in power in relation to each other.